2010
DOI: 10.1038/ajg.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Pregnancies Fathered by Inflammatory Bowel Disease Patients Exposed to Thiopurines

Abstract: Our data do not support the practice of routinely recommending to male patients that they interrupt thiopurines when wanting to conceive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 24 publications
0
33
1
2
Order By: Relevance
“…Based on that study there was some concern about continuing the drug in male patients wishing to have children. Further publications did not confirm these findings (Francella, et al, 2003;Truel, et al 2010).…”
Section: Birth Outcome In Ibd Fathers On Immunosuppressive Drugscontrasting
confidence: 39%
“…Based on that study there was some concern about continuing the drug in male patients wishing to have children. Further publications did not confirm these findings (Francella, et al, 2003;Truel, et al 2010).…”
Section: Birth Outcome In Ibd Fathers On Immunosuppressive Drugscontrasting
confidence: 39%
“…Publications identified were on methotrexate [22], lamuvidine [23], thiopurines [2,24] such as mercaptopurine [25] and azathioprine, ribavirin [26] and the combination of ribavirin--IFNa B2 combination [27], antirheumatics [18] such as methotrexate, sulfasalazin and biologics, finasteride [28], paroxetine [5] and testosterone gel [29]. The results of these studies are often contradictive.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies are often contradictive. For instance, two studies on mercaptopurine use by fathers report an increase of pregnancy-related complications [25] or congenital anomalies [2] while another study found no increased risk [24].…”
Section: Discussionmentioning
confidence: 99%
“…55 Thiopurines and biologic therapies do not affect male fertility, and pregnancy outcomes are not adversely affected if the father is taking these medications. [55][56][57][58] However, men taking sulfasalazine or methotrexate should be warned of reversible oligospermia when trying to conceive. Fertility should be restored in men who stop taking methotrexate or sulfasalazine 3 months before trying to conceive.…”
Section: Pregnancy and Family Planningmentioning
confidence: 99%